Factors Determining Staphylococcus aureus Susceptibility to Photoantimicrobial Chemotherapy: RsbU Activity, Staphyloxanthin Level, and Membrane Fluidity - Kossakowska-Zwierucho, Monika; Kaźmierkiewicz, Rajmund; Bielawski, Krzysztof P.; Nakonieczna, Joanna (Frontiers in Microbiology, 2016)
Photoantimicrobial chemotherapy (PACT) constitutes a particular type of stress condition, in which bacterial cells induce a pleiotropic and as yet unexplored effect. In light of this, the key master regulators are of putative significance to the overall phototoxic outcome. In Staphylococcus aureus, the alternative sigma factor σB controls the expression of genes involved in the response to environmental stress. We show that aberration of any sigB operon genes in S. aureus USA300 isogenic mutants causes a pronounced sensitization (>5 log10 reduction in CFU drop) to PACT with selected photosensitizers, namely protoporphyrin diarginate, zinc phthalocyanine and rose bengal. This effect is partly due to aberration-coupled staphyloxanthin synthesis inhibition. We identified frequent mutations in RsbU, a σB activator, in PACT-vulnerable clinical isolates of S. aureus, resulting in σB activity impairment. Locations of significant changes in protein structure (IS256 insertion, early STOP codon occurrence, substitutions A230T and A276D) were shown in a theoretical model of S. aureus RsbU. As a phenotypic hallmark of PACT-vulnerable S. aureus strains, we observed an increased fluidity of bacterial cell membrane, which is a result of staphyloxanthin content and other yet unidentified factors. Our research indicates σB as a promising target of adjunctive antimicrobial therapy and suggests that enhanced cell membrane fluidity may be an adjuvant strategy in photoantimicrobial chemotherapy.